Superficial siderosis of the central nervous system is a rare and possibly underdiagnosed disorder - Yara Dadalti Fragoso; Tarso Adoni; Joseph Bruno Bidin Brooks; Sidney Gomes; Marcus Vinicius Magno Goncalves; Cassio Lemos Jovem; Andre Palma da Cunha Matta; Joao Filipe Oliveira; Fabio Siquinelli; Carlos Bernardo Tauil; Guilherme Navarro Troiani; Paulo Roberto Wille (Arquivos de Neuro-Psiquiatria)
ABSTRACT Superficial siderosis (SS) of the central nervous system (CNS) is a rare and possibly underdiagnosed disorder resulting from chronic or intermittent bleeding into the subarachnoid space, leading to deposition of blood products in the subpial layers of the meninges. Magnetic resonance imaging (MRI) shows a characteristic curvilinear pattern of hypointensity on its blood-sensitive sequences. Methods Series of cases collected from Brazilian centers. Results We studied 13 cases of patients presenting with progressive histories of neurological dysfunction caused by SS-CNS. The most frequent clinical findings in these patients were progressive gait ataxia, hearing loss, hyperreflexia and cognitive dysfunction. The diagnoses of SS-CNS were made seven months to 30 years after the disease onset. Conclusion SS-CNS is a rare disease that may remain undiagnosed for long periods. Awareness of this condition is essential for the clinician.